Preparation of educational videos doctors for skills training of students in the course of medicine for the treatment of gestational hypertension (Research, Society and Development, 2020)
Simulation is important to develop medical student expertise and care and provide a safe and controlled learning environment for training. In addition to developing essential medical skills, compatible with what is expected in training professionals to meet modern health demands. This article reports the experience of developing educational videos for teaching skills related to medical care and procedures directed at gestational hypertension, in order to enhance learning and strengthen the theoretical and practical basis of these skills. The main objective of this work was to develop videos as a teaching resource for graduate medical students.